Measuring HPV vaccination coverage in Australia: comparing two alternative population‐based denominators - Bianca Barbaro; Julia M.L. Brotherton (Elsevier, 2015)
Abstract Objective: To compare the use of two alternative population‐based denominators in calculating HPV vaccine coverage in Australia by age groups, jurisdiction and remoteness areas. Method: Data from the National HPV Vaccination Program Register (NHVPR) were analysed at Local Government Area (LGA) level, by state/territory and by the Australian Standard Geographical Classification Remoteness Structure. The proportion of females vaccinated was calculated using both the ABS ERP and Medicare enrolments as the denominator. Results: HPV vaccine coverage estimates were slightly higher using Medicare enrolments than using the ABS estimated resident population nationally (70.8% compared with 70.4% for 12 to 17‐year‐old females, and 33.3% compared with 31.9% for 18 to 26‐year‐old females, respectively.) The greatest differences in coverage were found in the remote areas of Australia. Conclusion: There is minimal difference between coverage estimates made using the two denominators except in Remote and Very Remote areas where small residential populations make interpretation more difficult. Adoption of Medicare enrolments for the denominator in the ongoing program would make minimal, if any, difference to routine coverage estimates.